2018
DOI: 10.1111/ppl.12714
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and hormonal description of rootlet primordium development along white lupin cluster root

Abstract: Cluster root (CR) is one of the most spectacular plant developmental adaptations to hostile environment. It can be found in a few species from a dozen botanical families, including white lupin (Lupinus albus) in the Fabaceae family. These amazing structures are produced in phosphate‐deprived conditions and are made of hundreds of short roots also known as rootlets. White lupin is the only crop bearing CRs and is considered as the model species for CR studies. However, little information is available on CRs aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The formation of cluster roots and carboxylate exudation induced by low P availability have been studied extensively in L. albus (Shane et al, 2003b;Wasaki et al, 2003;Shen et al, 2005;Li et al, 2008;Cheng et al, 2014;Gallardo et al, 2019), and many species of Proteaceae like Hakea sp. (Lamont, 1972a,b), Grevillea robusta (Skene et al, 1996(Skene et al, , 1998, H. prostrata (Shane et al, 2003a), Grevillea crithmifolia (Shane and Lambers, 2006), and Euplassa cantareirae (de Britto Costa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of cluster roots and carboxylate exudation induced by low P availability have been studied extensively in L. albus (Shane et al, 2003b;Wasaki et al, 2003;Shen et al, 2005;Li et al, 2008;Cheng et al, 2014;Gallardo et al, 2019), and many species of Proteaceae like Hakea sp. (Lamont, 1972a,b), Grevillea robusta (Skene et al, 1996(Skene et al, , 1998, H. prostrata (Shane et al, 2003a), Grevillea crithmifolia (Shane and Lambers, 2006), and Euplassa cantareirae (de Britto Costa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(lupini) makes lupins highly efficient atmospheric nitrogen fixers (Fernández-Pascual et al 2007;Peix et al 2015). Additionally, white lupin is capable of forming specialized cluster roots which release carboxylates to mobilize poorly available phosphorus sources (Gallardo et al 2019;Lambers et al 2013). White lupin is recognized for its high protein content (36 to 38%), starch-free white seeds, outstanding fatty acid quality and additional health benefits, making its grains ideal for the food and feed industry (Arnoldi et al 2015;Boschin et al 2008;Monteiro et al 2014).…”
mentioning
confidence: 99%
“…PGPRs reportedly enhance RWC and dry matter through increasing choline production as a precursor to glycine betaine (as a means of osmotic regulation) (Vurukonda et al 2016). Alternatively, bacterially-produced indole acetic acid (Table 1) might improve leaf water content through enhanced root growth (Gallardo et al 2018) and soil water absorption. Barnawal et al (2017) reported that, compared to non-inoculated plants, PGPRs inoculated ones exhibited enhanced stomatal conductance under stressful conditions, possibly indicating the effects of these bacteria on maintaining plant water content due to optimal stomata conductance.…”
Section: Discussionmentioning
confidence: 99%